The Influence of Minority Stress on Level of Depression among Thai LGBT Adults - Priyoth Kittiteerasack; Alana Steffen; Alicia Matthews (Jurnal Keperawatan Indonesia, 2020)
In the US, lesbian, gay, bisexual, and transgender (LGBT) individuals report higher rates of depression compared with heterosexual and cisgender persons. To date, little is known about the mental health of LGBT adults in Thailand. Here, we examined rates and correlates of depression among a volunteer sample of Thai LGBTs. Data were collected as part of a larger cross-sectional survey study. Standardized measures of sexual orientation and gender identity, stress, coping style, and minority stressors were completed. Of the 411 participants, 40.3% met the criteria for depression. In multivariate analyses, the combined influences of sociodemographic factors, general stress, coping strategies, and minority-specific stress variables explained 47.2% of the variance in depression scores (F[16,367]= 20.48, p<.001). Correlates of depression included coping strategies and minority-specific stressors, including experiences of victimization, discrimination, and level of identity concealment. Study findings have implications for psychiatric nursing practice and the development of intervention research. Abstrak Pengaruh Stres Minoritas terhadap Tingkat Depresi pada LGBT Thailand. Di AS, individu lesbian, gay, biseksual, dan transgender (LGBT) melaporkan tingkat depresi yang lebih tinggi dibandingkan dengan orang heteroseksual dan cisgender. Saat ini, sedikit yang diketahui tentang kesehatan mental pada orang dewasa dengan LGBT di Thailand. Di sini, kami meneliti tingkat dan korelasi depresi di antara sampel sukarelawan LGBT Thailand. Data dikumpulkan sebagai bagian dari studi survei cross-sectional yang lebih besar. Pengukuran terstandar terhadap orientasi seksual dan identitas gender, stres, koping, dan stresor minoritas telah selesai. Dari 411 peserta, 40,3% memenuhi kriteria untuk depresi. Dalam analisis multivariat, pengaruh gabungan faktor sosiodemografi, stres umum, strategi koping, dan variabel stres spesifik-minoritas menjelaskan 47,2% dari varians dalam skor depresi (F [16,367]= 20,48, p< 0,001). Korelasi depresi termasuk strategi koping dan stres spesifik-minoritas, termasuk pengalaman viktimisasi, diskriminasi, dan tingkat penyembunyian identitas. Temuan penelitian memiliki implikasi untuk praktik keperawatan psikiatris dan pengembangan penelitian intervensi. Kata kunci: depresi, LGBT, minoritas seksual dan gender; stres minoritas, Thailand